Little women - Alcott, Louisa May, 1832-1888; Bailey, Ella (Surrey : Alma Classics, 2016)
Christmas won't be the same this year for Meg, Jo, Beth, and Amy, as their father is away fighting in the Civil War and the family has fallen on hard times. But though they may be poor, life for the four March sisters is rich with color, as they play games, put on wild theatricals, make new friends, argue, grapple with their vices, learn from their mistakes, nurse each other through sickness and disappointments, and get into all sorts of trouble.
Keywords: Sisters -- Fiction; New England -- History -- 19th century -- Fiction; Domestic fiction